114 Features of fibromyalgia in lupus nephritis. (April 2019) - Rogers, Jennifer L; Eudy, Amanda M; Criscione-Schreiber, Lisa G; Pisetsky, David S; Doss, Jayanth; Sun, Kai; Clowse, Megan EB
Abstract : Background: Patients with SLE have poor health related quality of life (HRQoL), however the predominant causes for decreased HRQoL in different subgroups of SLE are not well understood. Features of fibromyalgia, including fatigue, widespread pain, depression, sleep and cognitive dysfunction, are prevalent in SLE affecting 20%–65% of patients and often contribute to disability and poor health related quality of life (HRQoL). These aspects of fibromyalgia have not been well described in lupus nephritis (LN). We evaluated self-reported symptoms of fibromyalgia and mood disorders in patients with and without lupus nephritis Methods: This was a cross sectional study of SLE patients (ACR 1997 or SLICC 2012 criteria) from July to November 2018. All patients completed Systemic Lupus Activity Questionnaire (SLAQ), Patient Health Questionnaire-9 (PHQ9), and 2016 ACR Fibromyalgia criteria. Active nephritis was defined as UPC>500 mg and/or active urinary sediment excluding other causes. Fibromyalgia was defined as 7 areas of pain with 5 symptoms severity score (SSS) or 4 areas of pain with 9 SSS. Differences across groups were analyzed by Fishers exact test and ANOVA. Results: 205 patients completed patient reported outcome measures (92% female, mean age 45.1 years). In our cohort 17% had active nephritis, 16% were in nephritis remission and 67% had no history of nephritis. Of patients with nephritis, 28% had membranous class V, 27% had proliferative or proliferative/mixed LN, 3% class I/II, 0.5% post-transplant, 0.5% ESRD on dialysis, and class was unknown in 32%. The prevalence of fibromyalgia was 10.5% in those with nephritis compared to 23% of patients without nephritis (p=0.04). Patients with LN had statistically significantly lower fibromyalgia severity scores, symptom severity scores, areas of pain, fatigue, cognitive dysfunction, sleep disturbance, forgetfulness, muscle pain, and numbness. Patient-reported disease activity was significantly lower in patients with LN remission. Depression and anxiety were not significantly different between groups. Conclusions: Patients with both active and inactive lupus nephritis have lower rates of fibromyalgia, fatigue, sleep and cognitive dysfunction compared to non-nephritis lupus patients. Depression and anxiety were pervasive among all lupus groups and persisted even after achieving lower disease activity. The drivers of low HRQoL may be distinct across SLE subgroups. Lupus nephritis patients have high rates of disability and poor HRQoL, however the mechanism underlying these outcomes in nephritis is less likely related to features of fibromyalgia Funding Source(s): None